Meningkatkan Keterampilan Anggota BUMDes Dahlia melalui Pengolahan Limbah Dan Penyusunan Laporan Keuangan - yenni agustina; Kiagus Andi; Dewi Sukmasari; Reni Oktavia (Penerbit Goodwood, 2022)
Purpose: The primary purpose of the service's activity is to improve the soft-skills and hard skills of Dahlia Bumdes participants. The reason why it has already done because village-owned enterprises are business entities formed with the aim of improving the welfare of the community. Therefore, it is necessary to develop innovative products so that this can become other sources of business income. The resources that can be used and easier to get is cooking oil waste. However, many people do not know the waste treatment technique so as to produce products that have economic value. Method: This service activity uses several techniques. The initial stage that the team did was conducting a pre-survey. After that, the team did socialization about the plan to government in this village. The next stage is training. At this stage, the team used a persuasive approach, namely an invitation about the importance of awareness of the dangers of waste and the economic potential from processing waste into goods of economics value. The last approach is cognitive, namely in the form of training to improve the knowledge and skills of participants. Result: This activity received a positive response from both BUMDes and participants. It is clear that the participant was being enthusiastic toward training activity. Based on the results of the post-test given orally, there was an increase in the participants' cognitive abilities in answering the team's questions. Conclusion: The training activities had had a positive impact on the participants, especially in increasing the participants' cognitive knowledge and skills in processing waste materials and preparing financial reports.